Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Connie Klein, Robert Klein, Marilyn Benck, Ernie Benck, Fran Christiansen, Jim Christiansen, and Christine Watkins